The diffuse associationism in the territory: Between the formality and informality of the entities of the social economy in Mexico - González Rivera, Tatiana Vanessa (Cooperativismo & Desarrollo, 2022)
In the Social Sector of the Economy in Mexico despite recognizing, at the constitutional level and in its secundary law, different forms of expression; we identify academic and regulatory efforts focused strictly on cooperatives. This study is represent a significant contribution thanks to the analysis of other associative figures of the Social and Solidarity Economy, exposing its most important characteristics and advantages. On the other hand, from the approaches we have had with groups and collectives in the sector; from the Project "Nodess Morelos Solidarity and Cooperative" endorsed by the Institute of Social Economy of the government of Mexico and which purpose is to promote ecosystems of Social and Solidarity Economy in the country; We identify a diffuse associationism based on the convergence of emerging and resistance experiences that wander between formality and informality; Therefore, the analysis also tries to expose this panorama and the reasons put forward by some of these experiences, which allows us to derive suggestions that can contribute to the visibility and promotion of the sector.
Keywords: associationism; formality; Mexico; social sector of the economy